The case of the stalking moon [large type] - Wolfe, Ethan J. (Wolfe, Ethan J. Illinois Detective Agency, 2022)
"On the night of the full moon in Wyoming Territory, somebody dies a horrible and ghastly death by being scalped. For months, the territory is held by the grip of fear and Governor Hale turns to Charles Porter, founder of the Illinois Detective Agency, for help. Porters two top agents, James Duffy and Jack Cavill, are on holiday with their lady friends, so Porter assigns Joe Charles and Tom Adcock and scout/tracker Joseph Goodluck, a Mexican Comanche, to the assignment. Charles, Adcock, and Goodluck report to Governor Hale in Wyoming Territory. The most recent full-moon killing took place just a week earlier at the ranch owned by Ben Foster, located north of the capital in Cheyenne. From the Foster Ranch, Goodluck tracks the mystery killer northeast into South Dakota where it appears the trail leads to the Pine Ridge Indian Reservation. Goodluck leaves Adcock and Charles behind, as they are not allowed on the reservation, and he visits with the Lakota people to see if they know anything about the scalping and murders. Goodluck learns nothing on the reservation and returns to Adcock and Charles to find they have been scalped and murdered. Goodluck returns to Governor Hale with the news, which sends people all across Wyoming Territory into a panic. Farmers and ranchers leave the territory and Hale fears statehood will be delayed for decades. Charles Porter sends emergency telegrams to Duffy and Cavill to return to the office at once. When Duffy and Cavill arrive, they are reunited with Goodluck, and the men travel to Wyoming to hunt down the mysterious full-moon killer, known by the people as the ghost killer"--"--